2019
DOI: 10.1021/acsanm.9b00446
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Proton Conductivity of Sulfonated Polysulfone Membranes under Low Humidity via the Incorporation of Multifunctional Graphene Oxide

Abstract: Development of proton exchange membranes with sufficiently high proton conductivity, especially at low relative humidity (RH), remains a big challenge in the field of fuel cells. In this study, graphene oxide-based nanoscale ionic materials (NIMs-GO) were prepared by sulfonation with 3-(trihydroxysilyl)-1-propane­sulfonic acid and subsequent neutralization with amino-terminated polyoxypropylene (PO)–polyoxyethylene (EO) block copolymer. The resultant NIMs-GO with acid–base pairs and hygroscopic EO units were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 54 publications
0
31
0
Order By: Relevance
“…It also exhibits moderate reactivity in aromatic electrophilic substitutions and biocompatibility. [36][37][38][39][40] Polysulfone/polyaniline-poly(vinyl pyrrolidone) (PANI-PVP) nanocomposite facilitate water diffusion into the membrane pore and enhanced the hydrophilicity. 41 Polyaniline blended with polysulfone prepared by solution casting method exhibited moderately enhanced water hydrophilicity and used as a promising candidate for water filtration membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also exhibits moderate reactivity in aromatic electrophilic substitutions and biocompatibility. [36][37][38][39][40] Polysulfone/polyaniline-poly(vinyl pyrrolidone) (PANI-PVP) nanocomposite facilitate water diffusion into the membrane pore and enhanced the hydrophilicity. 41 Polyaniline blended with polysulfone prepared by solution casting method exhibited moderately enhanced water hydrophilicity and used as a promising candidate for water filtration membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Polysulfone (PSU) is an interesting aromatic polymer that possesses good physicochemical properties with excellent thermal and oxidative stabilities. It also exhibits moderate reactivity in aromatic electrophilic substitutions and biocompatibility 36–40 …”
Section: Introductionmentioning
confidence: 99%
“…The SGO-2.5 results were superimposable to the ones of Nafion ® 212. One should notice that the extrapolated values for the commercial material were larger than the typical results reported in the literature, which were about 0.1 S cm −1 [ 1 , 51 , 52 , 53 ]. Such an inconsistency could be ascribed to the condensation of water droplets on the surface of the stainless-steel electrodes during the tests, which could have altered the final measurements.…”
Section: Resultsmentioning
confidence: 60%
“…In addition, the obtained PEMFCs results were much better than the commercially existing Nafion ® 117 membranes. Jinzhao Li et al reported graphene oxide-based nanoscale ionic materials (NIMs-GO) by sulfonation with 3-(trihydroxysilyl)-1-propanesulfonic acid (SIT) and consequent neutralization with amino-terminated poly-oxypropylene (PO)-polyoxyethylene (EO) block co-polymer [70]. The schematic illustration of the NIMs-GO synthesis is depicted in Figure 5(A1).…”
Section: Membranes Derived From Polysulfone and Its Composites For Pe...mentioning
confidence: 99%